Silam Sakma, Indigenous Culture, and Ethnomathematics - Pradhan, Jaya Bishnu; Rai, Hem Bahadur; Acharya, Umesh (Journal of Mathematics Education, 2026)
Silam Sakma, a symbol of the Limbu community, embodies both cultural heritage and ethnomathematical knowledge. This study explores the connection between the construction of Silam Sakma and the application of fundamental - geometric concepts such as symmetry, rhombuses, squares, and the relationship between parallel and perpendicular lines. Traditionally crafted from bamboo or silk, Silam Sakma reflects a deep concept of geometry with patterns and craftsmanship. By examining this indigenous practice, the study highlights how the Silam Sakma as an ethnomathematical artifact integrates culture into modern education to enhance students' understanding of mathematics while preserving cultural and ethnic identity. The research emphasizes the importance of safeguarding traditional knowledge and fostering a culturally relevant educational practice. Silam Sakma stands as a testament to the Limbu community's resilience, serving both as a protective symbol and as a bridge between cultural traditions and an artifact for mathematical education for future generations.